MENINGKATKAN GERAK DASAR PENCAK SILAT KUDA-KUDA TENGAH KANGKANG DENGAN ALAT BANTU - Anggraheni Ambar Wardani; Usman Adam; Akor Sitepu (JUPE (Jurnal Penjaskesrek), 2013)
This study aims to determine the improvement of learning outcomes basic motion martial arts middle straddle horses with tools. That is the cycle of the rope aids anchored on both the side of the thigh when the student movement straddle the middle horses. Then the second cycle seat (school) who was appointed at the time the horses movement straddle the center in order to withstand the form of the horses remain consistent. And third cycles comrade carrying a heavy and almost the same height in the VB graders SD Muhammadiyah 1 Bandar Lampung in the Academic Year 2011/2012. The method used in this study is action research methods class (Class room Action Reserch), with three cycles, where in every cycle using different. Results of this study showed an increase in the basic motor skills of martial arts middle straddle horses through the use of tools in each cycle, while the increase at each cycle are as follows initial test 18.42%, 47.37% for unity cycle, the second cycle of 60.52%, and 92.1% for the third cycle.Kata kunci: pencak silat, kuda kuda tengah kangkang, alat bantu pencak silat